Active Role of ZnO Nanorods in Thermomechanical and Barrier Performance of Poly(vinyl alcohol-co-ethylene) Formulations for Flexible Packaging - Luzi, Francesca (Polymers (Basel), 2019)
Poly(vinyl alcohol-co-ethylene) (EVOH) films containing zinc oxide nanorods (ZnO Nrods) at 0.1, 0.5, and 1 wt%, were realized by solvent casting. The effect of ZnO Nrods content on morphological, thermal, optical, mechanical, and oxygen permeability properties were analyzed. In addition, moisture content and accelerated-aging test studies were performed, with the intention to determine the influence of zinc oxide nanofillers on the functional characteristics of realized packaging systems. Tensile properties showed increased values for strength and deformation-at-break in EVOH-based formulations reinforced with 0.1 and 0.5 wt% of zinc oxide nanorods. Results from the colorimetric and transparency investigations underlined that the presence of ZnO Nrods in EVOH copolymer did not induce evident alterations. In addition, after the accelerated-aging test, the colorimetric test confirmed the possibility for these materials to be used in the packaging sector. This behavior was induced by the presence of zinc oxide nanofillers that act as a UV block that made them useful as an efficient absorber of UV radiation.